Spatial Variability of Abyssal Nitrifying Microbes in the North-Eastern Clarion-Clipperton Zone - Hollingsworth, Anita L.; Jones, Daniel O. B.; Young, C. Robert (Frontiers in Marine Science, 2021)
Abyssal microbes drive biogeochemical cycles, regulate fluxes of energy and contribute to organic carbon production and remineralization. Therefore, characterizing the spatial variability of benthic microbes is important for understanding their roles in benthic environments and for conducting baseline assessments of areas of the seabed that might be targeted by commercial mining activities. Yet, detailed assessments of the spatial distributions of benthic microbial communities in these regions are still incomplete, and these efforts have not yet considered the influence of seafloor topography and heterogeneity on microbial distributions across a range of scales. In this study, we investigated the composition and spatial variability of benthic microbial assemblages found in sediments and polymetallic nodules collected from the Clarion Clipperton Zone (CCZ) in the equatorial Pacific (4000–4300 m water depth). We used 16S rRNA gene sequences to characterize these communities. The upper 20 cm of abyssal sediments harbored diverse and distinctive microbial communities in both sediments and their associated polymetallic nodules, with high similarity across topographical areas of the seabed. Assemblage composition differed vertically through the sediment, by habitat and across small to mesoscales. Potential carbon-fixing microbes formed more than 25% relative abundance of sediment assemblages, which were dominated by ammonia-oxidizing Archaea Nitrosopumilus. Non-photosynthetic Cyanobacteria were more frequent in the deeper sediment layers and nodules. Sediment communities had a higher abundance of taxa involved in nitrogen cycling, such as Nitrosopumilus, Nitrospina, Nitrospira, AqS1 (Nitrosococcaceae), and methanogens wb1-A12 (NC10 phylum). In contrast, nodules were more enriched in Alphaproteobacteria, Gammaproteobacteria, Planctomycetes, Acidobacteria, Bacteroidetes, Nanoarchaeaeota, and Calditrichaeota. Microbes related to potential metal-cycling (Magnetospiraceae and Kiloniellaceae), organic carbon remineralization (Woeseia), and sulfur-oxidizing Thiohalorhabdaceae were also more enriched in nodules. Our results indicate that benthic microbial community composition is driven by sediment profile depth and seafloor heterogeneity at small and mesoscales. The most abundant microbial taxa within the sediments were nitrifying and putative carbon-fixing microbes, and may have key ecological roles in mediating biogeochemical cycles in this habitat.